Combustion Synthesis Ironmaking: Investigation on Required Carbon Amount in Raw Material from the Viewpoint of Adiabatic Flame Temperature Calculation - Keisuke Abe; Ade Kurniawan; Masafumi Sanada; Takahiro Nomura; Tomohiro Akiyama (Universitas Gadjah Mada, 2019)
Combustion synthesis (CS) is a simple and very fast method to synthesize a target material. New ironmaking method via the CS using carbon-infiltrated iron ore was proposed, and the possible conditions for the method were investigated. Adiabatic flame temperatures (Tad) of the CS reaction, maximum reachable temperatures in an adiabatic system, were calculated to estimate the sample temperature during the CS. To reach the adiabatic temperature of 1811 K, 23.9, 27.9, and 29.3 wt.%-C were required for Fe2O3, Fe3O4, and FeO, respectively. When the carbon amount is higher than the calculated one, molten iron which is separated from slag components should be obtained via the CS.